Answer :

On factorizing the above equation,





(3x – 5) × (x) = 6 × (x2 – 3x + 2)


3x2 – 5x = 6x2 – 18x + 6


6x2 – 3x2 – 18x + 5x + 12 = 0


3x2 - 13x + 12 = 0


3x2 - 9x - 4x + 12 = 0


3x(x - 3) -4(x - 3) = 0


(3x – 4)(x - 3) = 0


Solving the first part,


3x – 4 = 0


3x = 4


x = 4/3


Solving the second part,


x – 3 = 0


x = 3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics